MANAGING DIFFERENCES IN THE MULTIETHNIC COMMUNITIES OF SOUTH KAZAKHSTAN - SAVIN, Igor (CENTRAL ASIA AND THE CAUCASUS, 2012)
Kazakhstan is frequently looked upon as a country that has succeeded in harmonizing an extremely ethnically and confessionally diverse social environment. There are indeed reasons for such inferences, one in particular being the absence of open mass opposition among different groups of the population in the Republic of Kazakhstan. However, this in no way means that the country’s social development is entirely free of collisions or inter-group tension. Such conflict is apt to erupt whenever the government and society fail to react on time to the challenges arising in our ever complicated social world. In turn, the shortcomings of the local self-government system tend to sap faith in the fairness of government institutions and the invincibility of constitutional principles. As a result, ethnic mobilization is becoming an effective way to form and uphold particular group interests. So it stands to reason that the Assembly of the People of Kazakhstan is increasingly faced with the task of shifting the focus of its attention from ceremonial issues to everyday relations among the people.The aim of this article is to analyze the integration and disintegration of rural communities in which different ethnic groups reside and live side by side in the same territorial and social environment of South Kazakhstan, as well as ways for the government and society to optimize their relations.In order to achieve this aim, the following research tasks must be solved:1. Revealing how public requests form with respect to realizing specific ethnocultural rights of the residents of multiethnic rural settlements.2. Defining the factors that have the greatest influence on types of identity (general civil, local, and others) that predominate in the minds of the region’s residents.3. Identifying the role of the local power bodies in managing differences by analyzing several conflict situations.4. Drawing up recommendations for optimizing existing mechanisms and raising the effectiveness of their impact on the situation.We focused on the relations between three South Kazakhstan communities—Uzbek, Turkish (Ahiska Turks), and Kurdish—and the local power bodies.